Changes on food intake, body weight and salivary amylase synthesis in the submandibular gland of Wistar rats treated with Bevacizumab and cytostatics - Claudio Gastón Dubersarsky; Evelin Bachmeier; Catalina Melchora Francia; María Angélica Rivoira; Daniela Josefina Porta; Mabel Noemí Brunotto; Marcelo Adrián Mazzeo (Universidad de Concepción., 2024)
Background: Bevacizumab together with 5-fluorouracil and oxaliplatin inhibit microvascular growth of tumor blood vessels and tumor proliferation. Few reports state the effect of these therapeutic schemes on salivary glands. Materials and Methods: Food consumption, body weight and salivary amylase activity were assessed in the submandibular gland of rats. Adult male Wistar rats, of three months old with 350/400 grams body weight, under 12-hour light/dark cycles respectively, were divided into the following experimental groups: G1) Control group, G2) 5-Fluorouracil and leucovorin calcium treated group, G3) Bevacizumab treated group, G4) Oxaliplatin treated group, G5) Bevacizumab, oxaliplatin, 5-fluorouracil and leucovorin calcium treated group and G6) Drug-free paired feeding treated group. Assessment of treatment effect was performed by one-way ANOVA. A value of p<0.05 was set for statistical significance. Results: Salivary amylase activity in gland homogenate was G1: 137.9 ± 4.64, G2: 60.95±4.64, G3: 120.93 ± 4.96, G4: 26.17 ±4.64, G5: 10.77 ±4.64 and G6: 82.87 ±4.64 U/mg protein (mean ± S.D.) Amylase activity in the G1 group was higher relative to the other experimental groups p<0.0001. Conclusions: The drugs 5-fluorouracil and oxaliplatin altered salivary amylase activity by serous granules of the submandibular gland interpreted as a mechanism of impaired acinar function. Bevacizumab administered in isolation did not alter salivary amylase activity compared to the control group. While the lower intake of the matched feeding group affected salivary amylase activity compared to the control group, the effect was significantly greater in animals treated with the oncology drugs used in the present animal model.